2015
DOI: 10.3390/nu7095349
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Colonic Fermentation and Fecal Water Toxicity to the Pathophysiology of Lactose-Intolerance

Abstract: Whether or not abdominal symptoms occur in subjects with small intestinal lactose malabsorption might depend on differences in colonic fermentation. To evaluate this hypothesis, we collected fecal samples from subjects with lactose malabsorption with abdominal complaints (LM-IT, n = 11) and without abdominal complaints (LM-T, n = 8) and subjects with normal lactose digestion (NLD, n = 15). Lactose malabsorption was diagnosed using a 13C-lactose breath test. Colonic fermentation was characterized in fecal sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 28 publications
0
11
1
1
Order By: Relevance
“…In our results, we found that the concentrations of SCFAs in the cecal contents of the model group was significantly decreased compared with that of the control group, which was different from a previous study that showed that an increase in SCFAs resulted in acute ingestion of lactose in vivo and in vitro (He et al, 2006;Windey et al, 2015). Few studies have focused on the effect of chronic lactose intervention on SCFAs, and a recent study (Zhai et al, 2018) found no significant difference in the SCFA concentration of feces after 3 weeks of lactulose intervention in mice, suggesting a different mechanism between acute and chronic ingestion.…”
Section: Discussioncontrasting
confidence: 99%
“…In our results, we found that the concentrations of SCFAs in the cecal contents of the model group was significantly decreased compared with that of the control group, which was different from a previous study that showed that an increase in SCFAs resulted in acute ingestion of lactose in vivo and in vitro (He et al, 2006;Windey et al, 2015). Few studies have focused on the effect of chronic lactose intervention on SCFAs, and a recent study (Zhai et al, 2018) found no significant difference in the SCFA concentration of feces after 3 weeks of lactulose intervention in mice, suggesting a different mechanism between acute and chronic ingestion.…”
Section: Discussioncontrasting
confidence: 99%
“…Association of outcome with peak gas concentrations, rather than concentration‐time profiles, indicates maximum changes in intestinal distension to be more important for symptoms than total gas load or degree of malabsorption and fermentation . Visceral hypersensitivity due to either peripheral sensitisation or altered endogenous sensory modulation will pre‐dispose to increased symptoms with distension and may be triggered by chemosensitivity to a fermentation product . The resident intestinal microbiome is therefore likely to be an important determinant in FODMAP‐related symptoms and the outcome of a low‐FODMAP diet and a recent small study in children demonstrated a baseline microbiome with greater saccharolytic capacity was associated with a beneficial symptomatic response to a 48 h reduction in FODMAPs .…”
Section: Discussionmentioning
confidence: 99%
“…However, we did not demonstrate a clear relation between SCFA levels and IBS symptoms. Previous investigations have evidenced a possible link between microbial fermentation products and abdominal complaints, as well as extra-intestinal symptoms, both in human studies [8,25,26] and in animal models [27,28]. The major SCFAs - acetic, propionic and n-butyric acids - have been particularly incriminated.…”
Section: Discussionmentioning
confidence: 99%